The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.athoracsur.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Right-Sided Versus Left-Sided Pneumonectomy After Induction Therapy for Non-Small Cell Lung Cancer

Abstract: Background. A right-sided pneumonectomy after induction therapy for non-small cell lung cancer (NSCLC) has been shown to be associated with significant perioperative risk. We examined the effect of laterality on long-term survival after induction therapy and pneumonectomy using the National Cancer Data Base. Methods. Perioperative and long-term outcomes of patients who underwent pneumonectomy after induction chemotherapy, with or without radiotherapy, from 2004 to 2014 in the National Cancer Data Base were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
7
2
1
Order By: Relevance
“…Patients on this study experienced significant toxicity after EPP, which could have been exacerbated by decreased healing capacity due to neoadjuvant high-dose radiation. Compared to the 100% rate of grade 3+ post-operative toxicity observed on this study, previous reports of EPP for MPM without neoadjuvant radiation have reported 10-50% grade 3+ postoperative non-hematologic toxicity (4,12).…”
Section: Discussioncontrasting
confidence: 79%
“…Patients on this study experienced significant toxicity after EPP, which could have been exacerbated by decreased healing capacity due to neoadjuvant high-dose radiation. Compared to the 100% rate of grade 3+ post-operative toxicity observed on this study, previous reports of EPP for MPM without neoadjuvant radiation have reported 10-50% grade 3+ postoperative non-hematologic toxicity (4,12).…”
Section: Discussioncontrasting
confidence: 79%
“…However, after matching, 1-, 3-, and 5-year OS rates were 75.4%, 50.7%, and 41.0% and there was no signi cant difference between sides (P>0.05). The results of Yang et al [16] were similar, but they did not nd signi cant difference in 5-year survival rate between left and right PN before or after matching.…”
Section: Discussionmentioning
confidence: 70%
“…Riquet et al discovered that the overall survival after pneumonectomy among the 10-year survivors ( N = 250) could not be meaningfully distinguished by the laterality of tumor/surgery ( 14 ). Similarly, in 2019, Yang et al reported that right-sided or left-sided pneumonectomy after induction chemotherapy was not beneficial for long-term survival ( 23 ). Wang et al also analyzed the data of 100 cases with pneumonectomy and found that the right- or left-side resection didn't give a long-term survival benefit for those patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%